Analysis of cheese production plant from plant layout engineering practices.: Factors in plant design (Innovation & Development in Engineering and Applied Science, 2023)
This article discusses important considerations for designing the layout of a cheese production plant to maximize efficiency and productivity. The article reviews various principles and factors that influence plant layout design, including the Principle of the integrated whole, Principle of the minimum travel distance, Principle of circulation, Principle of cubic space, Principle of satisfaction and safety, Principle of flexibility, and machinery, human, movement, waiting, service, building, change, and material factors. The correct layout of a cheese production plant is essential for efficient and high-quality production. The application of the appropriate principles and factors can establish an optimal arrangement of the plant's elements, reduce downtime, minimize transport costs, and maximize available space. The article discusses each of the principles and factors in detail and establishes the most critical considerations for their application in designing the cheese production plant's layout. Proper application of these principles and factors can improve efficiency, productivity, and profitability in cheese production, contributing to the development of the food industry.
Keywords: Plant Layout; Principles; Factors; Cheese Production